Association Between MTHFR rs17367504 Polymorphism and Major Depressive Disorder in Taiwan: Evidence for Effect Modification by Exercise Habits - Hsieh, Ming-Hong; Nfor, Oswald Ndi; Ho, Chien-Chang; Hsu, Shu-Yi; Lee, Chun-Te; Jan, Cheng-Feng; Hsieh, Pao-Chun; Liaw, Yung-Po (Frontiers in Psychiatry, 2022)
Background/Aim: Recent studies reported that folate supplementation has beneficial effects on major depression. The Methylenetetrahydrofolate reductase (MTHFR) enzyme is crucial in folate metabolism. This population-based study examined the association between MTHFR rs17367504 polymorphism and major depressive disorder based on exercise habits. Methods: Taiwan Biobank (TWB) provided demographic and genotype data between 2008 and 2015. The biobank participants were Taiwanese aged 30 to 70. Data on major depressive disorder (MDD) were obtained from the National Health Insurance Research Database (NHIRD). Results: A total of 636 individuals were identified with MDD, whereas 17,298 individuals were considered controls. The associations of MTHFR rs17367504 and exercise with MDD risk were estimated using logistic regression models. The distribution of MTHFR rs17367504 genotype frequencies differed significantly between the MDD and control groups. We found that, compared with the AA genotype, the GG genotype was associated with a significantly increased risk of MDD [adjusted odds ratio (aOR), 1.76; 95% confidence interval (CI), 1.05–2.94; p = 0.033]. We found an interaction (p = 0.04) between rs17367504 and exercise, a well-known protective factor for MDD. A substantial increase in the risk of MDD was found among those with GG genotypes who did not exercise (aOR, 2.93; 95% CI, 1.66–5.17; p<0.001). Conclusions: Our findings indicate that MDD is related to MTHFR rs17367504 and exercise, though the mechanisms remain to be determined.